Effect of decompressive hemicraniectomy on mortality of malignant middle cerebral artery infarction - Bahram Aminmansour (Journal of Research in Medical Sciences, 2010)
Background: Increasing intracranial pressure (ICP) is one of the leading causes of mortality in patients with malignant infarction of the middle cerebral artery (MCA). We prospectively evaluated patients with MCA infarction for one month survival after decompressive hemicraniectomy. Methods: This study was conducted at Alzahra University Hospital, Isfahan (Iran). Twenty patients with infarction in total MCA distribution area, resulting in midline shift of brain tissue for greater than 5mm, underwent decompressive hemicraniectomy. Mortality rate was estimated one month after surgery. Results: Patients were 8 (40%) males and 12 (60%) females with a mean age of 49.9 ± 3.8 (25 to 70) years. Left and right MCA were involved in 7 (35%) and 13 (65%) patients, respectively. Four (20%) patients died within one month after surgery (3 females and one male, mean age of 59.0 ± 4.5 vs. 47.6 ± 3.4 in survived patients, p < 0.001). The mean of baseline Glasscow Coma Scale (GCS) score estimated 8.60 ± 1.55 in survived patients and 6.75 ± 0.95 in patients who died (p < 0.05). Conclusions: The survival rate of malignant MCA infarction treated with decompressive hemicraniectomy was the same as previous reports. MCA infarction mortality increased with age and lower admission GCS score.